Cellulose Microfibril from Banana Peels as a Nanoreinforcing Fillers for Zein Films - Phiriyawirut, Manisara; Maniaw, Parichat (Scientific Research, 2012)
Cellulose microfibril (CMF) was the extraction with acid mixture from peel of Musa sapientum Linn type of banana (Kluai Nam Wa). The fibrous-shape of CMF interconnected weblike structure with the average diameter 26 nm were observed by TEM. In order to prepare zein/CMF nanocomposite films, 16 wt% zein solution was prepared by dissolved in 80% ethanol aqueous solution which contain glycerol 20% w/w. The suspension of CMF and zein solution was mixed with 0% - 5% weight fractions of solid CMF in zein matrix. The morphology of the zein films is more roughness by increased amount of cellulose microfibrils. It was found that as CMF content increase from 0 to 5 wt% results in increasing tensile strength and Young’s modulus of zein nanocomposite films. The highest strength obtains at 4 wt% CMF.
Keywords: Zein; Cellulose Microfibril; Nanocomposite; Reinforcement